Multisensory learning system applying augmented reality - Guevara-Maldonado, César (2020)
Mathematics is essential in our daily life. However, traditional teaching methods are mainly limited to the use of textbooks, generating demotivation and low interest in learning the subject. The present study proposes the development of an augmented reality system for the multi-sensory learning of students in the field of mathematics. For the creation of this proposal, we have used a human–computer interface tool called Makey Makey. Besides, the Singapore method, which has produced excellent results in the learning of mathematics, is applied. Scratch, a programming language that allows people to develop applications without having deep knowledge of the code, was used for the development of the application. Scratch allows us to combine Singapore, Makey Makey, and Augmented Reality optimally for learning. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2020.